Fresno County Women Lawyers Annual Dinner: Honoring Mary Louise Frampton - Watkins, Howard::::::::: (1989)
Keynote speaker: 2nd District Court of Appeal Presiding Justice Arleigh Woods speaking at lectern looking to her left